Value Chain Analysis of Ngoc Linh Ginseng at Nam Tra My District, Quang Nam Province, Vietnam - Nguyen Thi Hanh; Nguyen Thi Huynh Nha; Ao Xuan Hoa (My University, 2024)
Value Chain Analysis of Ngoc Linh Ginseng at Nam Tra My District, Quang Nam Province, Vietnam
Keywords: Value chain